Arylation of Azlactones using Diaryliodonium Bromides and Silver Carbonate: Facile Access to α‐Tetrasubstituted Amino Acid Derivatives. Issue 11 (28th May 2014) - Chai, Zhuo; Wang, Biao; Chen, Jia‐Nan; Yang, Gaosheng
Abstract With the combined use of silver carbonate, diaryliodonium bromides were successfully utilized as aryl source to realize the highly efficient arylation of azlactones under mild conditions. The reaction worked well with various alkyl‐ and aryl‐substituted azlactones, providing a range of α‐tetrasubstituted amino acid derivatives in moderate to high yields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>